Dormancy Broken of Bintaro Seed (Cerbera manghas Linn.) - Edje Djamhuri; Yuli Hasmaliah (Jurnal Silvikultur Tropika, 2014)
Germination process of bintaro seed (Cerbera manghas Linn.) need a long time due to a mecanical dormancy. Initial treatment necessary to be done to broking a seed dormancy by soaking the fruit or seed in water. The aim of this study is to analyze effect of stripping fruit skin and soaking time of fruit on germination of bintaro seed., and to analyze effect of soaking time on germination of bintaro seed. The result shows that stripping of fruit skin and interaction stripping skin with soaking time is not significantly affected on all parameter of seed germination, while soaking time of bintaro fruit is significantly affected on germination capability and germination value, also significantly affected on germination speed and growth speed. Soaking time of bintaro fruit that is optimum in broaking seed dormancy is 3 weeks.Soaking time is significantly affected on germination capability, germination speed, and germination value. Soaking time of bintaro seed that is optimum in broaking seed dormancy is 6 hours. Germination bintaro seed can be done by firstly soaking a fruit in water for 3 weeks, or by firstly soaking the seed in water for 6 hours.